Aspects of the biology and fishery of redtail roundscad (Decapterus russelli) in the coastal water of Western Leyte - Caliente, Alejandro Cabansay
Some aspects of the biology and fishery of Redtail Roundscad (Decapterus russelli) caught in the coastal water of western Leyte were studied then compared with the previous findings obtained by Tiews et al (1968), Magnusson (1970) and Ingles and Pauly (1984). A total of 2,508 fish samples weighing around 85 kilograms were randomly collected monthly from October 1983 to October 1984 in selected ring net boats and fish landing centers of Western Leyte. Of these samples, 639 fishes were used for biological study. The study showed that D. russelli in Western Leyte were moderately large reaching an average length of 16.5 cm FL. Throughout the year the size composition of the catch was dominated by one distinct length class that progressively increased monthly to the next higher length class. Males and females were evenly distributed in size groups, gonadal maturity stages and seasonal occurrence in the catch. The length-weight relationship of this fish was expressed as W = 0.01480L2.9183. For males it was expressed as W = 0.01676L2.8642 while for females it was expressed as W = 0.01281L2.9806. It was found out that the females had the tendency to become more rotund than males as they grow longer. The average size at first maturity of D. russeli was 15.3 cm FL. This spawned from January to June with peak spawning occurring in March and May. Its fecundity ranged from 26,000 to 51,000 eggs at a corresponding length range of 16.0 to 25.00 cm FL. Its spawning habit was asynchronous in nature. D. russelli was carnivorous in food habit. When small (6-15 cm long, they were zooplankton feeders and when large (16-25 cm long) they become piscivorous. Their diet composition changed with the change of their body size and gonadal maturity. Parasite infestation of D. russelli was not observed in this study. The growth coefficient (K) of this fish was found to be high at 1.1 per year which seems to support the rough estimate of growth rate at 1.0 cm per month measured from a starting juvenile size of 6.0 cm long. The longevity of this fish was low (2.7 years). The population was composed of one cohort only and its recruitment pattern that occurred as one long pulse within the year attests to this. The mean size at first capture was 11.7 cm FL. The estimated total mortality (Z) was 2.84 per year with a corresponding natural mortality much higher (M=1.95/yr.) than the fishing mortality (F = 0.90/yr). The exploitation rate was estimated at E = 0.32. D. russelli was a major component of the catch landed by ring nets from 1981 to 1985. Its mean relative abundance in the Decapterus catch and in the total landed catch was around 65% and 32%, respectively. They were abundantly caught from January to May, with peak abundance occurring in April. The average annual catch per boat was estimated at 6.9 metric tons. The mean catch per boat per day was around 30 kilograms. A comparison of the findings obtained in tis study with that of the previous investigations showed that dissimilarities were noted in certain aspects of their growth, reproduction and fishery and almost entirely in the aspects of population parameters. The aspect on sex ratio, fecundity and food habits were noted to be distinctly similar.